2008
DOI: 10.1007/s00418-008-0395-x
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 induced activation of the apoptotic death-receptor pathway in human Jurkat T lymphocytes

Abstract: Galectin-1 (gal-1), a member of the family of beta-galactoside binding proteins, participates in several biological processes such as immunomodulation, cell adhesion, regulation of cell growth and apoptosis. The aim of this study was to investigate whether gal-1 interferes with the Fas (Apo-1/CD95)-associated apoptosis cascade in the T-cell lines Jurkat and MOLT-4. Gal-1 and an Apo-1 monoclonal antibody (mAb) induced DNA-fragmentation in Jurkat T-cells whereas MOLT-4 cells were resistant. Gal-1 stimulated DNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 45 publications
2
60
0
5
Order By: Relevance
“…The apoptotic effect of extracellular Gal-1 on activated T-cells has been described in a number of papers [3,4,6,24,30]. It has also been shown that T-cells express Gal-1 upon activation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The apoptotic effect of extracellular Gal-1 on activated T-cells has been described in a number of papers [3,4,6,24,30]. It has also been shown that T-cells express Gal-1 upon activation.…”
Section: Discussionmentioning
confidence: 97%
“…The result of these authors indicated that even if secreted, Gal-1 amount in unconcentrated supernatant could not be enough to exert cytotoxicity, since the concentration of soluble Gal-1 inducing T-cell death was shown to be between 25-400 g/ml in all published experiments [4,7,30,31]. Moreover, Gal-1 is normally present in serum only in very low quantity (several ng/ml), which is far below the apoptosis inducing concentration of the soluble protein [32].…”
Section: Discussionmentioning
confidence: 99%
“…accordingly we have recently described the crucial function of p56 lck and Zap70 in gal-1 induced t cell apoptosis [8,9]. our previous data [7][8][9] and those provided by other laboratories [1,10,21] support that it is a mitochondrial type of caspase-mediated cell death, however other researchers have shown that gal-1 triggers a mitochondrial route independent of the caspase cascade [5]. moreover, stowell et al [20] have published results indicating that gal-1 prepares leukocytes for phagocytic elimination by inducing phosphatidylserine exposure on the outer surface of the plasma membrane without stimulating apoptosis.…”
mentioning
confidence: 89%
“…data describing the mechanism of gal-1 induced t-cell apoptosis have been obtained using soluble, recombinant gal-1 and remained highly controversial [1,5,7,9,10,19]. the receptor tyrosine phosphatase cd45, initially described as apoptotic receptor for gal-1 [14,15,23] has recently been shown to be dispensable [4,11,12].…”
mentioning
confidence: 99%
“…The recombinant protein was active because it was capable of inducing apoptosis of Jurkat T cells (supplemental Fig. S3, B and C) (5,33,34). Using the solvent of galectin-1 protein as a control buffer, the recombinant galectin-1 was added into the culture medium of U937T…”
Section: Recombinant Galectin-1 Restores Hif-1␣-induced Differentiatimentioning
confidence: 99%